AN EPROM RESIDENT INTELLIGENT INTERFACE FOR ACCESS TO MULTIPLE BIBLIOGRAPHIC DATABASE SYSTEMS - Shepherd, Michael A.; Watters, Carolyn; Lee, Boon-Chok (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF